Impact of Prolonged use of Facemask on Healthcare Workers During COVID 19 Pandemic - Acharya, Alina; Manandhar, Sriti; Shrestha, Karuna; Ghimire, Srijana Sapkota; Luitel, Anish (Birat Journal of Health Sciences, 2024)
Introduction: The Novel coronavirus originated in Wuhan, China in December 2019. In March 2020, WHO had declared the outbreak of COVID 19 as a pandemic. The disease had spread to millions of individuals through respiratory droplets. It has challenged the health sector of the world. The medical professionals involved in its management are mandated to wear masks and personal protective equipment (PPE) for a prolonged period of time for their protection.Objective: To identify various ill effects of facemasks and its possible solutions which will inturn guide to decrease those effects and increase compliance of facemasks during COVID 19 pandemic.Methodology: This is a cross sectional study done in Birat Medical College and teaching hospital. All respondents filled up a specifically designed questionnaire containing fifteen questions which included various possible effects of facemasks.Results: A total of 103 health care providers working in Birat Medical College and teaching hospital were included in the study. Majority were female (56.3%). The mean age of individuals was 29.62 years. The most commonly used mask was surgical mask (95%).The common effects experienced were pain behind ears(76.1%), excessive sweating in perioral region(72.8%) and headache(70.9%).Some of them had generalized nasal discomfort(60.2%), nasal itching(41.7%), dry nose (20.4%) and skin rashes around lips(49.4%). 27.2% had acne over face and 16.5% had halitosis.Conclusion: Prolonged use of facemasks during COVID 19 has adverse effects like pain behind ears, excessive sweating in perioral region, headaches, acne.The solutions to these problems can be thought of in preparation for future pandemics. Frequent breaks, proper skin care of the face, improved hydration and designing of comfortable masks are recommended for future management of adverse effects related to its prolonged use.